Single Cell Analysis of Factor VIII-specific T Cells in Hemophilic Mice after Treatment with Human Factor VIII - Sasgary, Maria; Ahmad, Rafi U.; Schwarz, Hans Peter; Turecek, Peter L.; Reipert, Birgit M. (Thrombosis and Haemostasis, 2002)
A multi-parameter flow-cytometry assay was established suitable for analyzing T-cell-specific cell surface markers (CD3, CD4) together with intracellular cytokines on a single cell level. This assay was used to identify the frequency and the kinetic of different populations of factor VIII (FVIII)-specific CD4+ T cells in hemophilic E-17 mice after treatment with human FVIII. A clear temporal correlation was found between the appearance of FVIII-specific CD4+ T cells in the spleen and the detection of anti-FVIII antibodies in plasma. These cells and antibodies were detectable in all experiments after two doses of FVIII and in a few even after a single dose. The IFN-γ- producing T cells were the most prominent type of FVIII-specific T cells suggesting Th1-type T cells have an important role in regulating the anti-FVIII immune response in E-17 mice. IL-10-producing T cells were the second most dominant type. They were detectable after two doses of FVIII and increased in frequency after four. Cytokine co-expression studies analyzing IL-10 and IFN-γ- in the same cell indicated that there might be at least two types of IL-10 positive T cells, those cells that produce IL-10 only and in addition cells that produce IL-10 and IFN-γ-. Furthermore, FVIII-specific T cells producing IL-2 were found in all experiments after two doses of FVIII. In a few experiments IL-4-producing T cells were seen but in most experiments they were not detectable. In contrast, IL-4 could be found in supernatants of in vitro restimulated CD8– spleen cells.
Keywords: Hemophilia A; factor VIII; T cells; cytokines; flow cytometry